1989
DOI: 10.1007/bf01665963
|View full text |Cite
|
Sign up to set email alerts
|

THF-γ2, a thymic hormone, increases immunocompetence and survival in 5-fluorouracil-treated mice bearing MOPC-315 plasmacytoma

Abstract: The effect of the thymic hormone, THF-gamma 2, on the immunocompetence of 5-fluorouracil (5-FU)-treated BALB/c mice, bearing MOPC-315 tumor, was examined. Treatment of noninoculated or tumor-bearing mice with THF-gamma 2 after 5-FU injection, resulted in an increase in the antibody response to sheep red blood cells and in the allogeneic response in spleen cell cultures and had no effect on the concanavalin-A-induced interleukin-2 secretion beyond that caused by 5-FU alone. Treatment with either 5-FU alone or 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…Thymic hormones have been shown to increase T-cell differentiation and immunological competence in vitro and in vivo (Trainin et al, 1985;Goldstein et al, 1972) and to increase immunocompetence and survival in 5-FU-treated mice bearing MOPC-315 plasmacytoma (Ophyr et al, 1989). Thymosin alpha 1 (Tal), a synthetic thymic hormone, has been shown to promote IL-2 production by lymphocytes, to increase the expression of high-affinity IL-2 receptors and to accelerate in vivo differentiation of immature cells into cytotoxic effectors (Goldstein et al, 1972;Leichtling et al, 1990) increasing NK activity in chemotherapy or tumor-immunosuppressed mice (Favalli et al, 1989).…”
mentioning
confidence: 99%
“…Thymic hormones have been shown to increase T-cell differentiation and immunological competence in vitro and in vivo (Trainin et al, 1985;Goldstein et al, 1972) and to increase immunocompetence and survival in 5-FU-treated mice bearing MOPC-315 plasmacytoma (Ophyr et al, 1989). Thymosin alpha 1 (Tal), a synthetic thymic hormone, has been shown to promote IL-2 production by lymphocytes, to increase the expression of high-affinity IL-2 receptors and to accelerate in vivo differentiation of immature cells into cytotoxic effectors (Goldstein et al, 1972;Leichtling et al, 1990) increasing NK activity in chemotherapy or tumor-immunosuppressed mice (Favalli et al, 1989).…”
mentioning
confidence: 99%
“…Administration of THF-y2 increases immune competence in 5-FU-treated mice bearing MOPC-3 15 plasmacytoma (Ophir et al, 1989) and repairs the immunodeficiency of mice cured of MOPC-315 plasmacytoma by melphalan (Ophir et al, 1990). We now show the potential of a megadose of THF-y2 to improve the effectiveness of therapy when used in combination with immunosuppressive anticancer drugs.…”
Section: Discussionmentioning
confidence: 84%
“…Accordingly, it is conceivable that additional treatment with a T-cell modulator such as THF-y2 may improve the effectiveness of chemotherapy with alkylating drugs, under conditions in which chemotherapy alone is only partially effective. Such conditions administration (Ophir et al, 1989) prolonged the survival time of MOPC-315 TB mice. Either low doses of THF-y2 alone (Ophir et al, 1989), or megadoses of THF-y2 alone (data not shown), had no effect on survival time of mice bearing MOPC-3 15 tumors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations